Fan Culture dan Batasan Hukum: Analisis Tindakan Sasaeng Fans dalam Perspektif Hukum Pidana - Anggraeni, Hari Sri; Tohari, Mohamad; Susilowati, Tri (Universitas Muhammadiyah Ponorogo, 2025)
The phenomenon of sasaeng fans in the K-pop industry has become a serious issue that threatens the privacy and security of idols. Behaviors such as stalking, spreading personal information, and even physical threats are common actions of sasaeng fans, which are often difficult to address legally. This study analyzes sasaeng fans' behavior from the perspective of South Korean criminal law, focusing on case studies of BTS and NCT. The research employs a normative and empirical juridical approach, utilizing legal regulations, court decisions, news reports, and relevant case documentation as data sources. The findings reveal that although South Korea has implemented the Stalking Punishment Act and other regulations, their enforcement faces several challenges, including difficulties in proving intent, relatively lenient penalties, and idols’ reliance on agencies to report cases. Therefore, stricter policy revisions, active agency involvement in reporting violations, and fan education on ethical boundaries in idol support are necessary. The results of the study show that although South Korea has enacted the Stalking Punishment Act and other regulations related to the protection of public figures, its implementation still faces significant obstacles. The original findings in this study indicate that one of the roots of the problem is not merely the legal vacuum, but rather the gap between the existence of the law and legal awareness of both victims and law enforcement officers. In addition, the results of this study also reveal that the sanctions imposed on sasaeng perpetrators tend to be light and do not have a deterrent effect, so that the practice of violating privacy against idols remains widespread.